Pikillacta : the Wari Empire in Cuzco - McEwan, Gordon Francis (University of Iowa Press, 2005)
The origin of the first Andean imperial state has been the subject of lively debate for decades. Archaeological sites dating to the Peruvian Middle Horizon time period, a.d. 540 to 900, appear to give evidence for the emergence of an expansive empire that set the stage for the development of the later Inca state. This archaeological investigation of Pikillacta, the largest provincial site of Peru's pre-Inca Wari empire, provides essential background for interpreting the empire's political and cultural organization. With engineering skills rivaling those of the builders of Cuzco itself, the War.